Charting the course of depression care: a meta-analysis of reliability generalization of the patient health questionnaire (PHQ- 9) as the measure - Kenni Wojujutari Ajele; Erhabor Sunday Idemudia (Discover Mental Health)
Abstract Background Depression is a leading cause of disability worldwide, requiring reliable and adaptable screening tools. The Patient Health Questionnaire- 9 (PHQ- 9) is widely used, yet its reliability across diverse populations and cultural adaptations remains unclear. Objective This meta-analysis assessed the reliability generalization of the PHQ- 9 across different populations, settings, and cultural contexts to determine its applicability in global mental health assessments. Methods A reliability generalization (RG) meta-analysis was conducted on 60 studies with 232,147 participants. A random-effects model was used to estimate pooled internal consistency (Cronbach’s α) and test–retest reliability. Subgroup analyses examined the effects of administration modes, cultural adaptations, and study settings. Results The pooled Cronbach’s α was 0.86 (95% CI [0.85, 0.87]), indicating high internal consistency. Test–retest reliability, based on eight studies, was 0.82 (95% CI [0.74, 0.90]). Self-administered formats had the highest reliability (α = 0.87), while face-to-face interviews were lower (α = 0.80). Substantial heterogeneity (I2 = 99.3%) was observed. Conclusions The PHQ- 9 is a reliable depression screening tool globally, but significant heterogeneity highlights the need for continued cultural adaptation and validation to enhance its applicability across diverse contexts.